A review of Boreoheptagyia Brundin, 1966 (Chironomidae: Diamesinae) from East Asia and bordering territories, with the description of five new species - Makarchenko, Eugenyi A.; Endo, Kazuo; Wu, Jingyang; Wang, Xinhua (Zootaxa, 2008)
Five new species of Boreoheptagyia Brundin, B. alulasetosa Makarchenko, Wu et Wang, sp. n., B. ambigua Makarchenko, Wu et Wang, sp. n., B. nepalensis Makarchenko et Endo, sp. n., B. sasai Makarchenko et Endo, sp. n., and B. xinglongiensis Makarchenko, Wu et Wang, sp. n., from East Asia and bordering territories are described and figured as males. Six additional species are commented on: B. brevitarsis (Tokunaga), B. kurobebrevis (Sasa et Okazawa), B. rotunda Serra-Tosio, B. similis (Chaudhuri et Ghosh), B. tibetica Makarchenko et Wang, and B. unica Makarchenko. A key to the males of Boreoheptagyia from East Asia and bordering territories is presented.